Application of the theory of planned behavior to understand factors that affect the travel intentions of Filipino tourists on nature-based destinations amidst the covid-19 pandemic - Dondoyano, Elaine T.; Estiaga, Angela Joyce P.; Omalza, Alliyah M.; Pintor, Sheila Marie F. (2022.)
Tourism has always been a key economic sector in the Philippines, but with the onslaught of the COVID-19 pandemic, the risks of getting infected implicated numerous factors that affected tourists' behavior intent to engage in any sort of travel. The researchers decided to conduct a study on the application of Theory of Planned Behavior to understand factors that affect the travel intentions of Filipino tourists on nature-based destinations amidst the COVID-19 pandemic. analysis on the theoretical model was administered with the use of SPSS for testing the hypothesis in the relationship of constructs in the Theory of Planned Behavior Model and the Spearman Correlations Rank Test was used to determine the significant influence of attitudes, subjective norms, and perceived behavioral control towards tourists' intention to visit nature travel destinations.Results of this study reveal that attitude has the highest significance and correlation to behavioral intention ; that traveling by group instead of traveling alone is more preferred by tourists; and that perceived behavioral control seconded attitude in exhibiting agreeableness of salient behavioral towards the intention to travel.
Undergraduate Thesis (Bachelor of Science in Business Administration-Marketing). -- Iloilo City : University of the Philippines Visayas-College of Management, July 2022.